Type Synthesis of Gear-box in Wind Turbine - Qiu, Jun; Liu, Boxing; Dong, Huimin; Wang, Delun (Procedia computer science, 2017)
This paper describes the development of wind power in the world from 2000 to 2015 and the main technical routes of both international and Chinese wind turbine. The main current type of gear-box of wind turbine under different rated power are summarized, and the future types of gear-box with power split transmission are presented and will be predicted in the future wind turbines with more than 5MW. In order to obtain the new types of gear-box for 6W wind turbines, a new type synthesis approach is proposed by means of the state space method. Through the operation of the dual vectors of the internal and external meshing transmission units according to the connection rules of series, parallel and hybrid, the state equations of different gear transmission systems are derived. At last, an example of speed-increasing gear-box of 6MW wind turbine is taken to show the process of type synthesis, and 16 types are proposed for referring the construction design of 6MW wind turbine gear-box.